The Influence Of Collateral And Loan Term On Credit Decisions At The Swadharma Savings And Loans Cooperative Artha Gemilang In Blahbatuh District, Gianyar Regency - Made Ayu Desy Geriadi; Ni Luh Widyantari (International Journal of Management Research and Economics, 2024)
There is attention and problems encountered related to collateral and loan terms in credit decisions at the Swadharma Artha Gemilang Savings and Loans Cooperative in Blahbatuh District, Gianyar Regency. The aim of the research is to determine the effect of collateral and loan term simultaneously and partially on credit decisions at the Swadharma Artha Gemilang Du Savings and Loans Cooperative, Blahbatuh District, Gianyar Regency. The number of samples was determined using the Accidental Sampling method as many as 90 credit customers at the Swadharma Artha Gemilang Savings and Loans Cooperative in Blahbatuh District, Gianyar Regency. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, determination analysis, statistical analysis of the t test (t-test) and statistical analysis of the F test (F-test). The results of the research show that there is a positive and significant influence, both partially and simultaneously, between collateral and loan term on credit decisions at the Swadharma Artha Gemilang Savings and Loans Cooperative in Blahbatuh District, Gianyar Regency. Keywords: ,